Age Peculiarities of the Pro-inflammatory Component of Cytokine Profile in Chronic Odontogenic Infection Affected by Polymorbid Pathology - Gorelik, Svetlana G. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: This study aimed to study the features of pro-inflammatory component of the cytokine profile in chronic odontogenic infection affected by polymorbid pathology. Materials and Methods: The study included 251 people: 125 middle-aged people (40–49 years) and 126 elderly people (60–69 years). All the people included in the study were divided into groups: Group 1 - apparently healthy people (33 patients of middle age and 31 of elderly age); Group 2 - patients suffering from chronic apical periodontitis (CAP) in granulating form (31 middle-aged patients and 33 elderly age patients); Group 3 - patients with CAP and coronary heart disease (CHD) (30 patients of middle age and 32 of elderly age); and Group 4 - patients suffering from CAP, CHD, and type 2 diabetes (31 middle-aged patients and 33 elderly patients). In all patients of different ages, cytokine profile was studied in blood serum, oral fluid, and crevicular gingival fluid. Results: The level of tumor necrosis factor alpha (TNF-α) in the blood serum depends significantly on the presence of a combination of CAP and CHD, CAP, CHD, and type 2 diabetes. A significant increase in the level of TNF-α in the oral and gingival fluids was noted when associated with polymorbid background in people of both the age groups. In the isolated course of CAP in elderly patients, unlike middle-aged patients, there was a significant increase in the concentration of interleukin (IL)-1β in blood serum. The level of IL-6 in the oral and gingival fluids is indicative of the characteristics of the inflammatory immune response in patients with CAP. The serum levels of IL-8 in elderly people are significantly higher than in middle-aged people. The increase in polymorphism leads to a significant increase in the degree of IL main in terms of IL-8. Conclusion: Concentration of TNF-α in blood serum with CAP can serve as an integral measure of immune inflammation. The level of IL-1β in blood serum, oral fluid, and gingival fluid can be considered as an additional factor characterizing the pathological process in polymorbid pathology. The level of IL-6 in the oral and gingival fluids is indicative of the characteristics of inflammatory immune response in patients with CAP. The severity of proinflammatory reaction by concentration of IL-8 is age dependent with a tendency of significant increase in the transition from middle to elderly age